Review of Law & Economics (De Gruyter, 2005)
The Review of Law & Economics (RLE) is published in cooperation with the European Association of Law and Economics (EALE) and De Gruyter. The Review publishes theoretical and empirical interdisciplinary research in law and economics-related subjects. The Journal explores the various understandings that economic approaches shed on legal institutions.